Pengembangan Modul Kimia Berbasis PBL Terintegrasi Steam untuk Siswa MA di Lombok Timur - Anita, Baiq Anita Febriana (Indo-MathEdu Intellectuals Journal, 2026)
This research aims to develop a chemistry learning module that is feasible and effective for use in the learning process and to determine student responses to the module developed. The research method used is research and development (Research and Development) with stages including needs analysis, module design, product development, expert validation, small group trials and large group trials. The research instruments are validation sheets, student response questionnaires, and learning outcomes tests. The results of validation and trials show that the chemistry module developed is of very good quality. Student responses to the module showed a percentage of attractiveness of 85.25%, appropriateness of the module content of 84.31%, ease of use of 86.49%, and usefulness of the module of 84.33%, all of which were in the very good category. The trial results showed an increase in student learning outcomes, with an average score of 82 in the small group trial and increasing to 88 in the large group trial. This shows that the module developed is effective in increasing students' understanding of chemistry material. Based on the results of this research, it can be concluded that the chemistry learning module developed is suitable for use as supporting teaching material in the learning process because it is able to improve student learning outcomes and obtain positive responses from students.